2010
DOI: 10.1073/pnas.1005267107
|View full text |Cite
|
Sign up to set email alerts
|

Prion disease susceptibility is affected by β-structure folding propensity and local side-chain interactions in PrP

Abstract: Prion diseases occur when the normally α-helical prion protein (PrP) converts to a pathological β-structured state with prion infectivity (PrP Sc ). Exposure to PrP Sc from other mammals can catalyze this conversion. Evidence from experimental and accidental transmission of prions suggests that mammals vary in their prion disease susceptibility: Hamsters and mice show relatively high susceptibility, whereas rabbits, horses, and dogs show low susceptibility. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
146
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 45 publications
12
146
1
Order By: Relevance
“…Recently, some researchers (6,47,48,49,50,51,52) reported that the β2-α2 loop plays an important role to stabilize the structural stability of rabbit and horse prion proteins. This conclusion can be confirmed from the hydrogen bond, hydrophobic bond, and salt bridge databases on horse prion protein presented by this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some researchers (6,47,48,49,50,51,52) reported that the β2-α2 loop plays an important role to stabilize the structural stability of rabbit and horse prion proteins. This conclusion can be confirmed from the hydrogen bond, hydrophobic bond, and salt bridge databases on horse prion protein presented by this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Although β2-α2 loop rigidity was thought to potentiate PrP C to PrP Sc conversion (24), subsequent studies revealed that PrP C of species considered resistant to prions, including horses, also contained rigid β2-α2 loops (25)(26)(27). Adding additional complexity, Tg mice expressing mouse PrP C containing rigid β2-α2 loops from elk or horse PrP spontaneously developed prion diseases (28,29).…”
Section: Significancementioning
confidence: 99%
“…This screen revealed a feature in the elk prion protein, where all backbone amide group NMR signals of the β2−α2 loop are observable at 20°C and a 1 H resonance frequency of 750 MHz; the β2−α2 loop is, therefore, well-defined in the NMR structure (23). This observation attracted special interest in the context of the CWD crisis of deer and elk in North America (34-37) and was followed up by structural studies of WT and specifically designed variant prion proteins (24-26, 28, 38), in vivo experiments with transgenic mice (11,13,14,39,40), and in vitro studies of correlations between the β2-α2 loop amino acid sequence and the propensity of PrP C to undergo transitions to PrP Sc -related conformations (41)(42)(43). In connection with animal experiments relating to CWD, the term RL-PrP C was introduced for PrP C s forming a structurally well-defined β2−α2 loop in the solution NMR structure at 20°C (39).…”
Section: T Ransmissible Spongiform Encephalopathies (Tses) Includementioning
confidence: 99%